2017
DOI: 10.4049/jimmunol.1700382
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Signaling Is Required for Restricted Homing of Parenteral Tuberculosis Vaccine–Induced T Cells to Both the Lung Parenchyma and Airway

Abstract: Although most novel tuberculosis (TB) vaccines are designed for delivery via the muscle or skin for enhanced protection in the lung, it has remained poorly understood whether systemic vaccine-induced memory T cells can readily home to the lung mucosa prior to and shortly after pathogen exposure. We have investigated this issue by using a model of parenteral TB immunization and intravascular immunostaining. We find that systemically induced memory T cells are restricted to the blood vessels in the lung, unable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 58 publications
(143 reference statements)
6
59
1
Order By: Relevance
“…We also report that CXCR3 expression was present only on lung parenchymal CD4 + T cells following mucosal BCG vaccination, and that expression of this marker was highest on PD-1 + KLRG1 − lung parenchymal cells. This contrasts with recent studies 24,44 which describe induction of antigen-specific T cells expressing CXCR3 in the lung vasculature. However, these studies used systemic immunisation with a subunit or viral-vectored TB vaccine rather than BCG, and are therefore not directly comparable.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…We also report that CXCR3 expression was present only on lung parenchymal CD4 + T cells following mucosal BCG vaccination, and that expression of this marker was highest on PD-1 + KLRG1 − lung parenchymal cells. This contrasts with recent studies 24,44 which describe induction of antigen-specific T cells expressing CXCR3 in the lung vasculature. However, these studies used systemic immunisation with a subunit or viral-vectored TB vaccine rather than BCG, and are therefore not directly comparable.…”
Section: Discussioncontrasting
confidence: 80%
“…Mucosal, but not systemic BCG, induced antigen-specific CD4 + T cells in the broncho-alveolar space. In agreement with this finding, several studies have demonstrated that TB vaccines delivered to the lung mucosa are able to elicit a T cell response within the airway lumen and restrict replication of M. tb in the first week following infection [44][45][46][47][48][49][50][51] . The data presented here, combined with these reports, indicate that airway luminal T cells may be able to provide a first line of defence against M. tb infection and should be considered as a target population when designing new vaccination regimes 49 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, the CXCR3 chemokine receptor have been reported to be expressed on human lung T-cells and demonstrated to play a significant roles in T-cell homing to the lung parenchyma and ariway since CXCR3 inhibition prevents airway immune responses and vaccine-induced T cell entry to the lung mucosal compartments [75][76][77][78][79] . Here we showed that, as previously observed with our MEMOPI ® -based neoepitope cancer vaccine approach, several peptides induced viral-specific CD8 T cells expressing the E (CD103) and α1 (CD49a) integrins and the CD44 memory marker, altogether characteristic of Trm.…”
Section: Cd8 T-cell Epitopes Ex-vivo Reactivity In Asymptomatic and Cmentioning
confidence: 99%
“…Here we showed that metformin-treatment resulted in an increased (i) elicitation of Ag-specific CD8 + TCM in the tissues of BCG-vaccinated mice, (ii) TNFa secreting Ag-specific CD8 + TCM cells in the tissues of BCGvaccinated Mtb-challenged mice, and (iii) protection of BCG-immunized mice and guinea pig against Mtb challenge. Importantly, expression of CXCR3 by TB vaccine-specific CD8 + T cells is needed for their homing to the lung mucosa 62 . This raises the possibility of the presence of metformin-educated CD8 + T cells in different anatomical location within lung parenchyma, which is responsible for enhanced protective immunity.…”
Section: Discussionmentioning
confidence: 99%